Diabetic foot presentation and surgical outcome at Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan: a prospective review - Othman, M. Y.; Fuzi, N M H; Noh, C I; Che Ahmad, Aminudin (2010)
Objective: To review the presentation and its surgical outcome among diabetic foot patients at Hospital Raja Perempuan Zainab II (HRPZ II), Kota Bharu, Kelantan. Methodology: This is a prospective study of 35 diabetic foot patients who were admitted to orthopaedic wards of HRPZ II from April to May 2007. Subjects were interview for sensory neuropathy and peripheral vascular disease. The lesion was classified based on Wegner’s and King’s classification. Blood glucose level and HbA1c were reviewed. Subjects were followed up for the surgical outcome. Results: 18 male patient (51.4%) and 17 female patients (48.6%) were involved in the study with men age of 58.4 ± 7.8 yeas old. Most of them are Malay (91.4%, n=32). 33 (94.3) patients were known to have diabetes mellitus with median duration of 12 years (range of 1-30 years). 71.0% (n=22) had significant neuropathy and 12% (n=3) had significant peripheral vascular disease. 51.4% (n=18) were classified in Grade 4 Wegner’s and Stage 5 King’s. Mean glucometer at early presentation was 14.7 ± 5.1 mmol/L and mean random blood glucose was 14.3 ± 8.0 mmol/L. HbA1c results revealed that 82.3% (n=14) of them had HbA1c more 8.0%. 14.3% (n=5) of the patients were planned for major amputation and 25.7% (n=9) were planned for Ray’s amputation. Within the study period, two patients died due to septicaemia. Conclusion: Majority of patients presented at advanced stage problem with poor glucose control. Rate of amputation was 40.0% and 14.3% ended up with major amputation.